Executive Committee Minutes 2008-04-03 - Academic Senate:::::::::
Voluntary System of Accountability, University Strategic Plan and Responses from APC members, Academic Freedom Policy, Revision to M.A. in Organizational Development, Academic Calendar Guidelines, Course Outline Policy, Blood Bank Resolutions